2021
DOI: 10.14740/gr1439
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic Minorities and Low Socioeconomic Status Patients With Chronic Liver Disease Are at Greatest Risk of Being Uninsured

Abstract: Background Chronic liver disease (CLD) predominantly affects ethnic minorities and socially vulnerable populations, who have high prevalence of risk factors (e.g., suboptimal insurance coverage) predisposing to healthcare disparities. We evaluate prevalence and predictors of uninsured status among CLD adults, and secondarily, how this affects documented immunity or vaccination for hepatitis A virus (HAV) and hepatitis B virus (HBV). Methods Using 2011 - 2018 National He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Fourth, the data source of this study is limited to commercially and Medicare Advantage insured patients. Though, these findings may not apply to uninsured or Medicaid insured patients, approximately 70% of the US population are enrolled in commercial or Medicare Advantage insurance and captures an important proportion of the US population [ 76 ]. Data on large cohorts of patients with cirrhosis are limited since large, national data repositories of these patients currently do not exist.…”
Section: Discussionmentioning
confidence: 99%
“…Fourth, the data source of this study is limited to commercially and Medicare Advantage insured patients. Though, these findings may not apply to uninsured or Medicaid insured patients, approximately 70% of the US population are enrolled in commercial or Medicare Advantage insurance and captures an important proportion of the US population [ 76 ]. Data on large cohorts of patients with cirrhosis are limited since large, national data repositories of these patients currently do not exist.…”
Section: Discussionmentioning
confidence: 99%
“…While Hepatitis B viral load is considered one of the strongest predictors of HCC risk and can be managed with anti-viral medications, unfortunately, even in low-risk regions such as United States, roughly 3% of people currently living with chronic HBV are on treatment[ 14 , 21 ]. Several studies have shown the impact of socioeconomic status (SES) on health outcomes in cancer with populations of lower SES and less wealthy nations having significantly lower survival rates[ 32 , 59 - 61 ]. One retrospective analysis of European nations found nearly 20% variation in all-cancer relative survival between the least wealthy and most wealthy nations[ 61 ].…”
Section: Demographic Factorsmentioning
confidence: 99%